Grass. Understanding agro-based traditional knowledge of Sami indigenous group in northern Norway (Karasjok) and discovering a new way of making ethnographic film. - Ahmad, Masum (UiT Norges arktiske universitet, 2016)
Nature plays a great role in every society. In many cases it shapes the form of a society in every direction possible. Therefore the essence of different societies are different according to their geographic location. Also there are many elements in a single society that can be worth to study. I chose nature, land and farming. It can be said that I tried to do visual anthropology of nature. As a result my film does not contain too much conversations. I tried to make it talk by itself with some new experiments and with few conversations, with a lot of machine noise, with the voice of nature and with the sound of silence. A poetic representation of everyday life of a village farmer where land is hard. Summer is short and winter is long.